Dinámica poblacional y fenología del salivazo de los pastos Zulia carbonaria (Lallemand) (Homoptera: Cercopidae) en el valle geográfico del río Cauca, Colombia - Castro, U.; Morales Rodriguez, A.; Peck, DC (2005)
We studied the population fluctuation of nymphs, adults, eggs and natural enemies of the spittlebug Zulia carbonaria(Lallemand) (Homoptera: Cercopidae) associated with Brachiaria dictyoneura pastures of the Cauca River Valley, Colombia. Our objective was to describe spittlebug phenology under seasonal conditions of bimodal precipitation (March-May and September-November). Weekly, over two years, populations of spittlebugs and certain natural enemies were quantified using a sweep net (adults) and counts of nymphs in spittle masses. To obtain eggs and study their development, adult females were collected weekly and placed in petri dishes with moist filter paper to oviposit. In both survey years 3-4 generations of Z. carbonaria were documented with a mean life cycle of 66 days. Populations were most abundant in the first semester and decreased dramatically over the course of the second semester, even in the rainy months (September-November). Very few diapausing eggs were detected (0.5%). Natural enemies included the nymph predator Salpingogaster nigra Schiner (Diptera: Syrphidae), parasitic mites of adults (Acari: Erythraeidae) and fungi of various genera. Although Z. carbonaria synchronizes its life cycle with the rains of the first semester, no role of diapausing eggs was detected as is common in other spittlebug species under conditions of unimodal precipation. Possible explanations for this synchrony and for the scarcity of the insect under the rainy conditions of the second semester are discussed.